Implementation of Cold Pressed Soap in e-Commerce as a Platform for Business Development with Special Reference to Chennai City - Chakravarthi, V. Vinu; Prakash, V. Surya; Veeramani, G. (AMC Indian Journal of Entrepreneurship, 2019)
When a consumer is given multiple options of products to choose from, he has the freedom to choose the best among the alternatives. In the current e-Commerce era consumers are provided with multiple choice of products in their computer/smartphone screen and at the same time, sellers have the facility to showcase their products directly to the consumers, unlike the traditional model where there are a number of channels. Even to the extent of personalizing a product, and to offer products to the consumer directly, there are e-Commerce companies available. This study is based on a survey of asample of 75 from Chennai city to study the sale of cold pressed soap in e- Commerce platform. The result of the study showed that there was awareness and acceptance of cold pressed soap among consumers, and at the same time consumers are to be educated about cold pressed soap, as most of them believe that cold pressed soaps are chemical free soaps which are not good as some chemicals are also added in the process. Clarity in the content and showcasing various certifications to consumers will increase trust and make e-Commerce as a platform for cold pressed soap. Online consultation on suitably flavoured soap can help to scale up the business.